2018
DOI: 10.4037/ajcc2018957
|View full text |Cite
|
Sign up to set email alerts
|

Advancing In-Hospital Clinical Deterioration Prediction Models

Abstract: Background Early warning systems lack robust evidence that they improve patients’ outcomes, possibly because of their limitation of predicting binary rather than time-to-event outcomes. Objectives To compare the prediction accuracy of 2 statistical modeling strategies (logistic regression and Cox proportional hazards regression) and 2 machine learning strategies (random forest and random survival forest) for in-hospital cardiopulmonary arrest. Methods Retrospective cohort study with prediction model develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…We chose a random forest model, which is a nonparametric machine learning approach that has been shown to outperform other algorithms without the need for standardization or log-transformation of the input data [ 16 , 21 , 22 ]. We chose this model for the following reasons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose a random forest model, which is a nonparametric machine learning approach that has been shown to outperform other algorithms without the need for standardization or log-transformation of the input data [ 16 , 21 , 22 ]. We chose this model for the following reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Second, to obtain a straightforward interpretation of the prediction, we used a classification model rather than a time-to-event model. Classification models were shown to outperform time-to-event models in predicting hospital deterioration in [22].…”
Section: Strengthsmentioning
confidence: 99%
“…In many of these studies the predicted outcome was a defined event that could be easily detected, such as mortality, cardiac arrest, or ICU transfer. In other cases, the predicted end-point was a more complex condition, such as renal failure or sepsis, that required a rule-based algorithm for event tagging [16][17][18][19][20][21]. In most studies, although the rules for event tagging were specified, no details as to the reliability of the tagging, manual or automatic, were provided.…”
Section: Discussionmentioning
confidence: 99%
“…4 5 The average rate of mortality among in-patient admissions is around 2% in USA, 6 indicating the necessity of using clinical deterioration prediction models. 7 Moreover, a recent study has shown that some in-hospital deaths due to clinical deterioration can be avoided. 8 Vital signs including heart rate (HR), pulse rate (PR), respiratory rate (RR), oxygen saturation (SpO 2 ), blood pressure (BP), body temperature (TP) and Glasgow coma scale (GCS) are essential parts of the patients' monitoring process.…”
Section: Introductionmentioning
confidence: 99%
“… 4 5 The average rate of mortality among in-patient admissions is around 2% in USA, 6 indicating the necessity of using clinical deterioration prediction models. 7 Moreover, a recent study has shown that some in-hospital deaths due to clinical deterioration can be avoided. 8 …”
Section: Introductionmentioning
confidence: 99%